Solar Radiation Impact on Interior Pressure and Temperature of LPG Storage Tank in Baghdad Provence - Amori, Karima E.; Yahya , Hadeer M. (Journal of Petroleum Research and Studies, 2024)
This work is related to reducing the impact of incident solar radiation on the internal thermal conditions of the LPG tank. An experimental study was carried out to test the effectiveness of using new thermal insulation layer for liquefied petroleum gas (LPG) tanks to reduce the absorbed heat during the summer season in Baghdad. Semi-spherical perlite particles of size (0.1861 to 1.604 mm) were mixed homogeneously with the resin coating is used as the heat insulating layer. Two identical thermally insulated and non-insulated LPG tanks are tested to indicate the effect of the adopted thermal insulation under different operating conditions. The two tanks were field tested with LPG volumetric filling ratio of (80%, 70%, 50%, 20%) and exposed to the same environmental conditions. Experimental results indicated that the coating significantly reduced the increase in temperature and pressure in the tanks, thus ensuring effective protection for the tanks. Where the results showed that the approved thermal coating prevented an increase in temperature and pressure in the insulated tank by (18.6%, 25%), respectively, compared to the non-insulated tank in July 2022. The data obtained confirmed the improvement in the safety of LPG storage, meaning that the thermal coating It is an effective way to improve the storage and transportation of liquefied gas in hot summer days.